Credit Risk Dynamics and Credit Quality in the Banking Sector and FMCG Industry: Bibliometric Study and Content Analysis - Muhammad Rafi Jainuri; Aang Kunaifi (Journal of Social Research, 2026)
In an increasingly dynamic and uncertain global business landscape, risk management has become essential to maintaining operational continuity and institutional performance. This study examines the dynamics of credit risk and credit quality and their impact on institutional performance in the banking and Fast- Moving Consumer Goods (FMCG) sectors. The objective of this research is to analyze the dynamics of credit risk and credit quality in the banking and FMCG sectors, Explore the Shift in Research Focus Post the 2008 Global Financial crisis, and provide practical recommendations for more adaptive risk management. This study employed bibliometric and content analysis approaches to evaluate existing literature on credit risk in both sectors. The analysis also includes scholarly collaboration and research trends from 2008 to 2016. The findings indicate a sharp increase in academic interest in this topic following the 2008 financial crisis, peaking in 2016. Research focus has shifted from financial stability to the integration of credit risk within non-financial industries such as FMCG. The Battle of the analysis also reveals fragmented scholarly networks. This study emphasizes the importance of applying adaptive, data-driven, and integrated risk mitigation theories to support the resilience of both the financial and real sectors. The Battle of the findings contribute to the development of a cross-sectoral framework and provide practical recommendations for contextual risk management.